5.2^3/x/-2511=72
giúp mik với ak
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(x+3)3:3-1=-10
(x+3)3:3=1-10
(x+3)3:3=-9
(x+3)3=(-9).3
(x+3)3=-27
(x+3)3=33
x+3=3
x=3-3
x=0
Ta có : ( x + 3 ) 3 : 3 - 1 = -10
<=> ( x + 3 ) 3 : 3 = ( -10 ) + 1
<=> ( x + 3 ) 3 : 3 = ( -9)
<=> ( x + 3 )3 =(- 9 ) . 3
<=> ( x + 3 )3 = (-27 )
<=> x + 3 = (-3)
<=> x = ( - 3) - 3
<=> x = -6
Vậy x = -6
\(x\left(x-\frac{1}{3}\right)< 0\)
Để \(x\left(x-\frac{1}{3}\right)< 0\)thì x và \(x-\frac{1}{3}\)trái dấu nhau
Thấy \(x>x-\frac{1}{3}\)\(\Rightarrow\hept{\begin{cases}x>0\\x-\frac{1}{3}< 0\end{cases}\Rightarrow\hept{\begin{cases}x>0\\x< \frac{1}{3}\end{cases}\Leftrightarrow}0< x< \frac{1}{3}}\)
\(\Leftrightarrow8x^3-4x^2+16x^2-8x+14x-7=0\\ \Leftrightarrow\left(2x-1\right)\left(4x^2+8x+7\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}2x-1=0\\4x^2+8x+4+3=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}\\4\left(x+1\right)^2+3=0\left(\text{vô nghiệm}\right)\end{matrix}\right.\\ \Leftrightarrow x=\dfrac{1}{2}\)
\(\frac{2}{5}\times\frac{1}{2}-\frac{2}{5}\times\frac{1}{3}-\frac{2}{5}\times\)\(\frac{1}{6}\)
\(=\frac{2}{5}\times\left(\frac{1}{2}-\frac{1}{3}-\frac{1}{6}\right)\)
\(=\frac{2}{5}\times\frac{0}{6}\)
\(=\frac{2}{5}\times0\)
\(=0\)
\(\frac{2}{5}\times\frac{1}{2}-\frac{2}{5}\times\frac{1}{3}-\frac{2}{5}\times\frac{1}{6}\)
\(=\frac{2}{5}\times\left(\frac{1}{2}-\frac{1}{3}-\frac{1}{6}\right)\)
\(=\frac{2}{5}\times0\)
\(=0\)
\(\frac{x-2}{4}=\frac{5+x}{3}\)
\(\Leftrightarrow3\left(x-2\right)=4\left(5+x\right)\)
\(\Leftrightarrow3x-6=20+4x\)
\(\Leftrightarrow3x-4x=20+6\)
\(\Leftrightarrow-x=26\)
\(\Leftrightarrow x=-26\)
\(\Leftrightarrow x^2=36\Leftrightarrow\left[{}\begin{matrix}x=6\\x=-6\end{matrix}\right.\)
\(\dfrac{-4}{x}=\dfrac{-x}{9}hay\dfrac{-4}{x}=\dfrac{x}{-9}\)
\(\Rightarrow x.x=\left(-4\right).\left(-9\right)\)
\(\Rightarrow x^2=36\)
\(\Rightarrow x^2=6^2hoac\left(-6\right)^2\)
\(\Rightarrow x\in\left\{6;-6\right\}\)
5.23.|\(x\)| - 2511 = 72
5.8.|\(x\)| = 72 + 2511
40.|\(x\)| = 2583
|\(x\)| = 2583 : 40
|\(x\)| = 64,575
\(\left[{}\begin{matrix}x=-64,575\\x=64,575\end{matrix}\right.\)